Descriptive Analysis of the Characteristics of Proven Cases of Sexual Abuse in Victims With Intellectual Disabilities and Children With Typical Development in Spain - Vara, Alba (Journal of interpersonal violence, 2021)
Children and people with intellectual disability (ID) are considered to be highly vulnerable and in need of special protection against sexual abuse (SA). The objective of this work was to analyze the characteristics of cases of SA in children with typical development and in people with ID in Spain. To do so, 25 cases of each type that had been investigated by specialized groups of the Judicial Police of the Spanish Civil Guard and that had been classified as proven and confirmed by police and forensic-medical evidence were analyzed. The results allowed the establishment of the typical minor victim profile as Spanish female (76%), with an average age of 8.64 years. Typical victim with ID was characterized as being of Spanish, aged 20.28 years on average, without prior sexual experience, and similar percentages of males (40%) and females (60%). In both cases, the aggressor usually acted alone, was known to the victim, had an average age of 42 years, and without a history of sexual offenses. The most common child sexual crime was SA with penetration, practiced repeatedly, using strategies such as the use of force, authority, rewards, or secrecy. Victims with ID suffered sexual abuse with penetration, using force, authority, threats or blackmail. Finally, 36% of minors not disclose the events by only 8% of victims with ID. Spontaneity was found in the 40% first disclosure in both victims, with greater police evidence and greater recognition of guilt on behalf of the aggressors against victims without disabilities. Minors took an average of 26.26 days to report the facts, and victims with ID of 64.94. It is necessary to know more about these types of offenses to design appropriate prevention and detection programs.